Resilience Of Tenth Grade Students Of Boarding School SMA IT Nur Hidayah Sukoharjo - Khotimah, Anisah Khusnul; Kumaidi, K (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: The purpose of this study is to find out the resilience of the tenth grade students boarding school SMA IT Nur Hidayah Sukoharjo. Methodology: This research uses quantitative descriptive methods. Sampling using purposive random sampling method with samples of 50 schoolgirls. Data collection method using resiliency scale measurement tool is then described.Results: Based on the results shows that the majority of students of grade X boarding school HIGH school IT Nur Hidayah have a low level of resilience (38%), while the other students are at a very low level (22%), medium (18%), high (14%) And very high (8%) So that it can be concluded that X class boarding school has low resiliency.Applications/Originality/Value: resilience is needed in adolescence to turn negative experiences into positive ones especially needed for teen boarding schools.